Neointimal coverage of jailed side branches in coronary bifurcation lesions: an optical coherence tomography analysis. Issue 2 (March 2018) - Kume, Teruyoshi; Yamada, Ryotaro; Terumasa, Koyama; Tamada, Tomoko; Imai, Koichiro; Fukuhara, Kenzo; Goryo, Yutaka; Kawamura, Ai; Hiroshi, Okamoto; Neishi, Yoji; Uemura, Shiro
Abstract : Objectives: The jailed strut at the side-branch (SB) orifice may be a cause of delayed neointimal coverage and SB flow disturbance after single stenting to bifurcation. The aim of this study was to characterize the exact relationship between the jailed strut pattern at the SB orifice immediately after stent implantation and neointimal coverage of the jailed SB orifice in the chronic phase. Patients and methods: A total of 29 bifurcation (left anterior descending coronary artery and diagonal branch) lesions treated by optical coherence tomography-guide single-stent implantation and followed at 18 months after a percutaneous coronary intervention were included in this study. Results: Using three-dimensional optical coherence tomography images, the jailed stent strut pattern was classified into two groups on the basis of the presence of a stent strut link at the SB orifice (link group: n =11, and no-link group: n =18). SB orifice obstruction by neointima was significantly greater in the link group than in the no-link group during the 18-month follow-up period (26.8±21.9 vs. 9.5±22.1%, P =0.049). Conclusion: This single-center observational study with a small sample size showed that a jailed strut pattern at the SB orifice might be related to neointimal coverage of the SB orifice in bifurcation lesions treated with single-stent implantation. Further large-scale studies with long-term follow-up will be necessary to determine the exact relationship between the jailed strut pattern at the SB orifice and SB flow disturbance because of delayed neointimal coverage as well as clinical outcome.